A Low-Carbon Planning Model for Regional Power Systems with Generation-Load-Storage Coordination considering New Energy Resources' Consumption. (27th June 2022) - Chen, Huiyuan; Zhang, Hua; Dai, Qiqi; Wang, Wei; Wang, Min
Abstract : With the increase in the proportion of new energy resources being generated in the power system, it is necessary to plan the capacity configuration of the power supply side through the coordination of power generation, grid, load, and energy storage, to create a relatively controllable power generation output and ensure the safe and stable operation of the power system is a key problem that needs to be solved at present. Therefore, combined with national and regional policies and resource constraints in China, this paper firstly determines the requirements and boundary conditions of various power supply planning in the regional power system and proposes a "generation-grid-load-energy storage" coordination mode. Secondly, establish a regional power system coordination planning model considering the proportion of new energy consumption and low-carbon cost. Finally, in three scenarios with a high, medium, and low proportion of new energy resources, the new installed capacity configuration of regional power supply is optimized to verify the effectiveness of the proposed model and provides reference for regional power supply planning.